Fatigue of double-network hydrogels. (January 2018) - Zhang, Wenlei; Liu, Xiao; Wang, Jikun; Tang, Jingda; Hu, Jian; Lu, Tongqing; Suo, Zhigang
Highlights: Initiate the study of the fatigue behavior of the classic double network hydrogels. Damage accumulates over thousands of cycles for an uncut sample. Crack extends over thousands of cycles for a cut sample. Determine a fatigue threshold and compare with the Lake-Thomas model. Abstract: The discovery of tough hydrogels of many chemical compositions, and their emerging applications in medicine, clothing, and engineering, has raised a fundamental question: How do hydrogels behave under many cycles of stretch? This paper initiates the study of the fatigue behavior of the classic PAMPS/PAAM double network hydrogels discovered by Gong and her co-workers [25]. We reproduce the hydrogels, and prepare samples of two types, with or without a crack cut before the test. When an uncut sample is subject to cyclic stretches, internal damage accumulates over thousands of cycles until a steady state is reached. When a cut sample is subject to cyclic stretches, the crack extends cycle by cycle if the amplitude of stretch is above a certain value. A threshold of energy release rate exists, below which the crack remains stationary as the sample is cycled. We find a threshold around 400 J/m 2 for hydrogels containing PAAM networks of a low density of crosslinkers, and around 200 J/m 2 for hydrogels containing PAAM networks of a high density of crosslinkers. The experimental findings are compared to the Lake-Thomas model adapted to the double-network hydrogels.